PENGARUH KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN SANKSI PAJAK SEBAGAI VARIABEL INTERVENING - Wael, Achmad Ramly; Sososutiksno, christina; Engko, Cecilia (Jurnal Akuntansi, 2023)
This research aims to determine: (1) The influence of taxpayer awareness on taxpayer compliance, (2) The influence of taxpayer awareness on taxpayer compliance with tax sanctions as an intervening variable. The sample for this research is 100 individual taxpayers who carry out business activities and freelance work in Ambon City. The sampling technique uses the Slovin formula. Research data was collected using a questionnaire. The research results show that: (1) Taxpayer Awareness influences Taxpayer Compliance, (2) Tax Sanctions cannot mediate the influence of Taxpayer Awareness on Taxpayer Compliance